Impact of peri‐implant soft tissue characteristics on health and esthetics. Issue 1 (17th January 2023) - Monje, Alberto; González‐Martín, Oscar; Ávila‐Ortiz, Gustavo
Abstract: Objective: To review the impact of key peri‐implant soft tissue characteristics on health and esthetics. Main Considerations: The keratinized mucosa width (KMW), the mucosal thickness (MT), and the supracrestal tissue height (STH) are essential components of the peri‐implant soft tissue phenotype. An inadequate KMW (<2 mm) has been associated with local discomfort upon oral hygiene performance and increased risk for the onset of peri‐implant diseases. A minimum buccal MT (≥2 mm) is generally required to prevent esthetic issues related to the effect of transmucosal prosthetic elements on the color of the mucosa and can also contribute to long‐term mucosal stability. STH is directly related to marginal bone remodeling patterns during the early healing process that follows the connection of transmucosal prosthetic components. Short STH, generally defined as <3 mm, has been consistently associated with marginal bone loss resulting from the physiologic establishment of the mucosal seal. Insufficient STH may also derive into the fabrication of unfavorable transmucosal prosthetic contours, which frequently results in unpleasing esthetic outcomes and predisposes to submarginal biofilm accumulation. Peri‐implant soft tissue dehiscences (PISTDs) are a type of peri‐implant deformity that are associated with esthetic issues and often occur in sites presenting KMW, MT, and/or STH deficiencies. PISTDs should be correctly diagnosed and treated accordingly, usually by means of multidisciplinary therapy. Conclusion: Understanding the impact of different dimensional and morphologic features of the peri‐implant mucosa on health and esthetic outcomes is fundamental to make appropriate clinical decisions in the context of tooth replacement therapy with implant‐supported prostheses.